KEBIJAKAN SEKOLAH DALAM PENGGUNAAN GADGET DI SEKOLAH DASAR - Agung Rimba Kurniawan; Faizal Chan; M Sargandi; Stevie Yolanda; Resty Karomah; Wuri Setianingtyas; Sintia Irani (LP3M STKIP Muhammadiyah Muara Bungo, 2019)
This study aims to find out, study, and describe school policies on the use of gadgets in SDN 13/I Rengas Condong and is expected to be able to find the right policies towards the use of gadget by students in schools. This research uses a qualitative approach. Data collected using observation, interviews, and documentation. The results of this study showed that students not allowed to bring gadget to school. But researcher found there are still students who bring gadget to school. This is because of the lack of control by the teacher, headmaster, or staf of school.